Analysis of Acceptance of E-Learning Users of Universitas Bhinneka PGRI Using the UTAUT Method - Renzy Praha Nandiva Renzy; Yayak Kartika Sari; Joko Iskandar (LPPM Universitas Bina Sarana Informatika, 2026)
The development of educational technology encourages the application of digital learning systems to support learning activities to take place more optimally and save time. Universitas Bhinneka PGRI has implemented the Learning Management System (LMS) as a means of supporting the digital learning system. A study of the level of user acceptance needs to be carried out to identify various influential factors so that they can be used for development according to developments based on the UTAUT method. This study aims to analyze the factors that affect LMS acceptance in users at Bhinneka PGRI Tulungagung University using the UTAUT method. This study uses a quantitative approach with a survey research type involving 95 users as a sample selected by purposive sampling technique. Data were collected through questionnaires with a likert scale of 1-5 and analyzed using the SEM-PLS method which included outer model test, inner model, and hypothesis test. This research resulted in LMS acceptance at UBHI which was quite good. This is shown by Performance Expectancy having a positive and significant influence on Behavioral Intention of 0.235. Effort Expectancy was 0.298, and Social Influence was 0.445. In addition, Behavioral Intention had a positive and significant effect on Use Behavior with a value of 0.673. Meanwhile, Facilitating Conditions had a positive but insignificant effect on Use Behavior with a coefficient value of 0.134. This study concludes that the use of LMS is influenced by the perception of benefits, ease of use, and social environmental support, compared to supporting facilities. This research contributes theoretically to the development of the UTAUT model and practically as an evaluation of improving the quality of LMS in universities.